GERMINATION, GROWTH AND NUTRITIONAL VALUE OF CORN FODDER APPLIED WITH KUSUM TREE (SCHLEICHERA OLEOSA) LIQUID SMOKE - Vertygo, Stormy; Paga, Agustinus; Abarca, Euridice Leyequien (LPPM Universitas Jambi, 2025)
Fodder is a high-yielding, space-efficient animal feed that can be harvested in a short period, making it crucial for sustainable livestock nutrition. However, improving both the growth and nutritional content of fodder remains a challenge. This study aimed to investigate the effects of liquid smoke application on the germination, growth, and nutritional quality of corn fodder. A Completely Randomized Design (CRD) was used, consisting of five treatments: seeds soaked in 0% (control, P0), 10% (P1), 20% (P2), 30% (P3), and 40% (P4) liquid smoke concentrations for 1 hour. The results showed that liquid smoke treatment did not significantly influence germination parameters, including Final Germination Percentage (FGP), Mean Germination Time (MGT), and Mean Germination Rate (MGR). However, significant effects were observed on growth indicators such as the number of leaves per sprout and dry weight. Furthermore, liquid smoke notably enhanced the crude protein and crude lipid content of the corn fodder, though it did not alter crude fiber levels.This study presents a novel approach to improving fodder quality using plant-derived smoke compounds, offering a simple, low-cost pre-treatment method for enhancing the nutritional profile of corn fodder. The findings imply that liquid smoke can serve as a natural biostimulant, potentially replacing or supplementing synthetic feed additives. Future research should explore the use of smoke water or direct plant-derived smoke under aerobic conditions to optimize germination and further boost fodder quality. These insights contribute to the development of more efficient and sustainable animal feed strategies.